Self-assembled micelles loaded with itraconazole as anti-Acanthamoeba nano-formulation - Rao, Komal; Abdullah, Muhammad; Usman, Ahmed *; Hashi, Isse Wehelie *; Shah, Muhammad Raza; Siddiqui, Ruqiayyah; Khan, Naveed A; Alawfi, Bader S; Ayaz, Anwar * (Springer, 2024)
Acanthamoeba castellanii are opportunistic pathogens known to cause infection of the central nervous system termed: granulomatous amoebic encephalitis, that mostly effects immunocompromised individuals, and a sight threatening keratitis, known as Acanthamoeba keratitis, which mostly affects contact lens wearers. The current treatment available is problematic, and is toxic. Herein, an amphiphilic star polymer with AB2 miktoarms [A = hydrophobic poly(ℇ-Caprolacton) and B = hydrophilic poly (ethylene glycol)] was synthesized by ring opening polymerization and CuI catalyzed azide-alkyne cycloaddition. Characterization by 1H and 13C NMR spectroscopy, size-exclusion chromatography and fluorescence spectroscopy was accomplished. The hydrophobic drug itraconazole (ITZ) was incorporated in self-assembled micellar structure of AB2 miktoarms through co-solvent evaporation. The properties of ITZ loaded (ITZ-PCL-PEG2) and blank micelles (PCL-PEG2) were investigated through zeta sizer, scanning electron microscopy and Fourier-transform infrared spectroscopy. Itraconazole alone (ITZ), polymer (DPB-PCL), empty polymeric micelles (PCL-PEG2) alone, and itraconazole loaded in polymeric micelles (ITZ-PCL-PEG2) were tested for anti-amoebic potential against Acanthamoeba, and the cytotoxicity on human cells were determined. The polymer was able to self-assemble in aqueous conditions and exhibited low value for critical micelle concentration (CMC) 0.05-0.06 µg/mL. The maximum entrapment efficiency of ITZ was 68%. Of note, ITZ, DPB, PCL-PEG2 and ITZ-PCL-PEG2 inhibited amoebae trophozoites by 37.34%, 36.30%, 35.77%, and 68.24%, respectively, as compared to controls. Moreover, ITZ-PCL-PEG2 revealed limited cytotoxicity against human keratinocyte cells. These results are indicative that ITZ-PCL-PEG2 micelle show significantly better anti-amoebic effects as compared to ITZ alone and thus should be investigated further in vivo to determine its clinical potential.